A study on prevalence and co-morbidity of bipolar and anxiety disorders in chronic headache patients - M., Sivaji; J., Manickavasagam; Sundaramurthi, Indumathi; S., Gopinathan (International Journal of Research in Medical Sciences, 2017)
Background: Co morbidity between headache and psychiatric disorders is more prevalent in chronic headache patients. The bipolar disorders and anxiety disorders are predominant in migraine and TTH respectively. This co morbidities have a poor reflection and impact on quality and outcome of chronic headache patients and results in worst prognosis and poor response to medical treatment. Methods: The chronic headache patients especially migraine and tension type of headache were analyzed with following materials such as the structured psychiatric clinical interview with ICD-10 mental and behavioural disorder, DSM-5 criteria. HAM-A, HAM-D, BDI-2, BPRS, young mania rating scale, Yale-Brown Obsessive Compulsive Scale (Y-BOCS) and panic disorder scale. Results: Various subsets of bipolar disorder and anxiety disorder were found as follows: 74% of migraineurs are associated with psychiatric disorders in which bipolar affective disorder 6%, depressive episode 48%, dysthymia 30%, GAD 10% and Panic disorder 6%. 52% of TTH are associated with psychiatric disorders as follows: major depressive episode 52%, GAD 30%, separation anxiety disorder 6%, PTSD 7%, OCD 3% and panic disorder 2%. Conclusions: From previous and future studies the headache can be identified according to subsets of headache with psychiatric disorders make easier to provide appropriate pharmacological and psychological treatment which may reduce the chronicity and intractability of headache.